The Information in Discretionary Outlays: Advertising, Research, and Development - Bublitz, Bruce; Ettredge, Michael (The Accounting Review, 1989)
[Recent studies have considered the association between abnormal stock returns and forecast errors of various components of earnings. For discretionary outlays such as advertising or research and development (R&D), the sign and magnitude of the association between forecast errors and abnormal returns can provide information concerning the expected duration of benefits arising from these activities. This empirical study compares market reaction to advertising and R&D forecast errors with market reaction to forecast errors for conventional expenses, and with a theoretical benchmark for long-lived assets. The results are mixed, but on balance the evidence is consistent with a market assessment that advertising is short-lived while R&D is long-lived.]